Performance and antrhropometric characteristics of Elite Rugby Players - Pasin, Federico; Caroli, Barbara; Spigoni, Valentina; Dei Cas, Alessandra; Volpi, Riccardo; Galli, Carlo; Passeri, Giovanni (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the study. Physical performance is the result of a complex combination of several factors such as genetic and anthropometric aspects, nutrition and hormonal status. In the past few years many studies have considered the impact of vitamin D on muscular strength and athletic performance.The aim of the present study was to assess the anthropometric measures impacting on physical performance in a group of professional rugby athletes.  As a secondary aim we investigated a possible relationship between baseline vitamin D status and athletic performance status in these subjects.Methods. All rugby players completed a test–retest reliability study on performance measures, as 70kg jump squat and body weight (BW) jump squat to assess musculoskeletal performance. Additionally at the time point we collected a blood sample of every athletes for the assessment of serum vitamin D.Results. We found that lean mass was an important independent predictor of performance score in 70kg jump squat (p=0.007, R2=0.74) and BW jump squat (p=0.010, R2=0.66) in these well trained athletes. No statistically significant association was present between performance score and serum vitamin D in this specific setting.Conclusions. We demonstrate a positive interaction between lower limb lean mass and performance score, but we have not been able to identify any statistically significant association between worsening in performance measures and decrease of serum 25 OH Vitamin D.